Rectenna design for electromagnetic energy harvesting and wireless power transfer - K. Singh, V; K. Singh, N; Kumar, Rahul; Yadav, Arun; Soo Chae, Gyoo; Sharma, Ashis; Kumar Bhoi, Akash (International Journal of Engineering and Technology, 2018)
Under this article,an antenna with rectifier circuit is intended and simulated to energize the wireless feeler systems at resonant fre-quency 5.3838 GHz. The antenna substrate is prepared with textile material. The dielectric constant of material is 1.7.The rectenna circuit has been simulated on the Jeans substance and examined for power level -5dBm. The presented antenna has a gain of 4.861 dBi. The anticipated antenna is designed with CST software. The value of L and C are calculated from MATLAB programming.